Psikoedukasi pencegahan kecanduan game online pada siswa kelas IX SMP Negeri 9 Kota Salatiga - Ramadanti Putri Mahanani; Khatrin Wandelmud Sailana; Sofia Mariska Rehiara; Enjang Wahyuningrum (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2026)
Online games are one form of technology utilization that is widely used as a source of entertainment. However, uncontrolled use of online games can lead individuals to develop addiction. Adolescents are a group that is vulnerable to online game addiction because at this age individuals often use their free time to play games in between their learning activities. If excessive gaming behavior cannot be controlled, it may lead to addiction and have negative impacts on adolescents. This activity is a form of community service aimed at increasing students’ knowledge about the prevention of online game addiction through psychoeducation. The activity was conducted with ninth-grade students of SMP Negeri 9 Salatiga. The methods used in this activity were counseling and interactive discussions about the impacts and prevention of online game addiction. The evaluation of the activity was carried out using a pre-test and post-test to determine changes in students’ level of knowledge. The results of the analysis using a T-test with the help of SPSS version 25 showed that the mean pre-test score was 9.10 and the mean post-test score was 9.35. The statistical test results indicated that the increase in scores was not significant, with a significance value of 0.161 (p > 0.05). Nevertheless, the psychoeducation activity still provided students with an initial understanding of the impacts and prevention of online game addiction. Therefore, similar activities are recommended to use more interactive methods and engaging educational media to improve the effectiveness did not have a significant impact on students' knowledge about online game addiction. Recommendations that can be given to improve the effectiveness of psychoeducation are by paying attention to the creation of pre- and post-test questions, using a supportive room, adding interactive media such as educational games and extending the duration of psychoeducation.